Types of underfit stream valleys on the territory of Belarus - Kalicki, Tomasz; Sanko, Aleksander F.; Trifonov, Yury Yu. (Journal of the Belarusian State University. Geography and Geology, 2019)
According to the materials of geological and geomorphological mapping and the results of the analysis of remote sen sing data (ERS), the authors identify several types of valleys of underfit rivers in Belarus. They differ from each other according to their relief, features of sediment accumulation and stages of postglacial evolution of river valleys. Their sections are located in the section of the meltwater valleys and within outwash plains. Authors distinguish: Dnieperian type (one active and one dead channel of the valley), Drutian type (narrow fluvial and wide non-fluvial zones within one valley, the valley bends may resemble the channel bends of the palaeo-river that formed the valley), West Berezinian type with erosion and non-erosion variant (all stages of river development are presented – from braided channels through large mean ders to small meanders), the Palaeo-Islochian type (dead river channels, including meandering on the outwash plains).
Keywords: geomorphology; underfit streams; valley evolution; valley typing; Earth remote sensing